Effect of Artemisia vulgaris Extract for Increasing IL-12 and Granzyme Expression (Study on Mammary Adenocarcinoma C3H Mice Given Adriamycin- Cyclophosphamide Chemotherapy Regimen) - Hardanto, Gery Rifano; Selamat Budijitno (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
Background: The incidence of breast cancer worldwide is still high. Surgery remains the top choice with other modalities of chemotherapy, radiation, and immunotherapy such as Artemisia vulgaris (AV). The study was aimed to demonstrate that administration of AV extract increased p53 expression and the apoptotic index in mammary adenocarcinoma. Methods: This study used a